Gambaran Tingkat Pengetahuan dan Sikap Kesiapsiagaan Masyarakat di Daerah Kekeringan Desa Jemowo Kabupaten Boyolali - Wahyu Sejati; Eska Dwi Prajayanti (An-Najat, 2024)
Drought is a natural disaster with the main characteristic of decreasing water availability in certain areas for a certain period of time. Drought is a complex and recurring natural hazard with different impacts on each region. The drought caused by the climate that prevails in the territory of Indonesia is the monsoon which is known to be very sensitive to changes in ENSO or El-Nino Southern Oscillation. To determine the level of knowledge and attitude of drought disaster preparedness in the community in Jemowo Village, Boyolali Regency. Type of qualitative descriptive research. The number of samples was 72 respondents with sampling using purposive sampling and statified random sampling. Univariate analysis showed the characteristics of the respondents, namely some of the age of the community is 33-45 years old (40.3%), elementary school education (66.7%), male (59.7%), farmer work (79.2%), preparedness knowledge in the good category (52.8%) and community preparedness attitude in the sufficient category (95.8%). The level of knowledge about drought disaster preparedness in the people of Jemowo Village is relatively good and the efforts of BPBD by conducting socialization and clean water assistance are very effective anticipating drought disasters.